Analisis Faktor-Faktor Keuangan Yang Mempengaruhi Market Share Perbankan Syariah Di Indonesia - Zakia Midania; Renil Septiano (JURNAL PUNDI, 2023)
This research aims to analyze the Effect of Operational Fee (BOPO), Return On Assets (ROA) and Financing to Deposit Ratio (FDR) against Market Share Syariah Bank in Indonesia. This type of research is quantitative. Total population of 11 Sharia General Banks. The technique of sampling used is a total sampling, where the number of samples is equal to the population, namely 11 General Bank Syariah, the number of samples is 33 samples obtained from 11 Common Bank Syariah during the period of 3 years, 2018 until 2020. The analysis technique used in this research is a double linear regression analysis using program assistance of SPSS versions 23. The pharmacy in the test by using the t test. The results of this study indicate that the variable Operating Cost of Operational Income (BOPO) and Return On Assets (ROA) has a significant effect on market share, while Financing to Deposit Ratio (FDR) does not significantly affect the dependent variables namely Market Share